Semaphorins in Adult Nervous System Plasticity and Disease - Carulli, Daniela; de Winter, Fred; Verhaagen, Joost (Frontiers in Synaptic Neuroscience, 2021)
Semaphorins, originally discovered as guidance cues for developing axons, are involved in many processes that shape the nervous system during development, from neuronal proliferation and migration to neuritogenesis and synapse formation. Interestingly, the expression of many Semaphorins persists after development. For instance, Semaphorin 3A is a component of perineuronal nets, the extracellular matrix structures enwrapping certain types of neurons in the adult CNS, which contribute to the closure of the critical period for plasticity. Semaphorin 3G and 4C play a crucial role in the control of adult hippocampal connectivity and memory processes, and Semaphorin 5A and 7A regulate adult neurogenesis. This evidence points to a role of Semaphorins in the regulation of adult neuronal plasticity. In this review, we address the distribution of Semaphorins in the adult nervous system and we discuss their function in physiological and pathological processes.